Volleyball coaches behavior assessment through systematic observation - Zetou, E.; Amprasi, E.; Michalopoulou, M.; Aggeloussis, N. (Journal of Human Sport & Exercise, 2011)
The purpose of this study was to record and evaluate the practice behaviors of 12 Greek Volleyball National Division coaches, mean age 47.36 (SD=6.1) through feedback that they provided to their athletes throughout the 2010-11 seasons. Verbal and non verbal behaviors were video recorded during four practices, of each coach. A total of 13.400 behaviors were observed and were coded using the Revised Coaching Behavior Recording Form which corresponded to the 12 categories of the instrument. The analyses of videotaped behaviors were made by two trained observers who were checked in the internal and external reliability. Results indicated that there were 279.11 coded coaching behaviors in each training session. A large proportion of reported coaching behaviors 17.38% (n=48.34) were about "Tactical Instruction", followed by "General Instruction" 15.92% (n=44.45) and "Technical Instruction" 12.42% (n=34.68). "Encouragement" and "Motivation" were 10.76% and 10.73% respectively. "Other Comments" (8.67%) and "Demonstration" (8.26%) were in lower rate. ANOVA revealed that there were not differences between 1st and 2nd division coaching behavior, instead of "Criticism" (p < 0.05) with 2nd division coaches have more comments and "Non verbal reward" (p < 0.05) which 1st division coaches were used more often.